Genetic Characterization of Escherichia coli O157 Isolated From Human Stool Specimens in Wassit Province of Iraq - Sabah M. Jwied; Mohammed Sh. Jebur (Journal of Techniques)
The goal of this study was to assess the severity of diarrhea caused by Shiga toxins produced by Escherichia coli ( STEC) isolated from human infections in Wassit province of Iraq. Stool specimens from (161) sporadic cases of diarrheal Patients with the mean age of (20 years), and  range from 1 month to 75 years, were collected in AL-Karamma Teaching Hospital   between March  to July 2019. Then they were processed by culture, microscopic tests and VITEK which were used for the identification as E. coli. PCR was performed for detecting shiga toxin genes in  E. coli isolates, and rfb gene (encoding O-antigene )   of STEC- O157. DNA sequencing was done on some positive isolates. The results of PCR detected stx genes in 19 (12 %) culture isolates of E. coli isolated from human diarrheal specimens. While 9 cases were positive for stx genes and have rfb gene. DNA sequences that depend on the sequence of the vtx2 gene have shown a highly homologous sequencing identity with NCBI-Blast Escherichia coli strain( O157:H7) isolates from humans and animals. The phylogenetic study revealed a clear genetic relationship between human and animal E. coli isolates and then gene sequencing was deposited with accession number into NCBI-Genbank (0MN944014.1). In conclusion, prevalence of E. coli O157 in humans remains undiagnosed because there are no traditional O157 detection methods in all our hospitals. Our study showed that the use of molecular methods in the detection can be used to detect STECs which cannot be detected using routine methods.